Ignoring Clustering and Nesting in Cluster Randomized Trials Renders Conclusions Unverifiable [Letter] - Siddique AB; Jamshidi-Naeini Y; Golzarri-Arroyo L; Allison DB (Risk Management and Healthcare Policy, 2022)
Abu Bakkar Siddique, Yasaman Jamshidi-Naeini, Lilian Golzarri-Arroyo, David B Allison Department of Epidemiology and Biostatistics, Indiana University School of Public Health-Bloomington, Bloomington, IN, USACorrespondence: David B Allison, Indiana University School of Public Health-Bloomington, 1025 E 7th St, PH 111, Bloomington, IN, 47405, USA, Tel +1 812 855-1250, Email allison@iu.edu Abu Bakkar Siddique, Indiana University School of Public Health-Bloomington, 1025 E 7th St, SPH 394, Bloomington, IN, 47405, USA, Tel +1 571 274-5328, Email abusiddi@iu.edu